(In)visibilização dos saberes de povos Afrikanos e de matriz afrikana : uma discussão sobre a decolonização curricular - Ndjungu, Abraão Nicodemos Chanhino (2024)
This research, titled ”(In)visibility of the knowledge of Afrikan matrix peoples: a discussion on curriculum decolonization,” aims to discuss how the knowledge of traditional Afrikan matrix populations relates to schools. We begin by examining the applicability of teaching Afro Brazilian History and Culture in schools, as established by Law 10.638-203 and the LDB, which call for the construction of an inclusive, anti-racist school that confronts colonialities—topics that should be considered in the process of curriculum development and in the Pedagogical Political Project (PPP). We engage with authors such as Fanon (2008), Oyewúmí (2002), Grosfoguel (2016), Noguera (2012), Santos (2006), Gomes (2013), (2014), and (2020), and Mbembe (2018), emphasizing that the epistemic racism present in the school curriculum ignores the knowledge of Afrikan diaspora students and teachers. Thus, we aim to broaden the debate on confronting racism and racial and epistemic inequality in schools, promoting emancipatory education connected to traditions present in Afro-Brazilian cultural spaces such as terreiros and quilombos, and fostering the production of Afrikan and Afro-diasporic intellectuality. This discussion helps to unveil the myth of racial democracy present in the formal curriculum, which promotes the exclusion and invisibility of the history and knowledge of these groups that have been historically erased from textbooks and schools, both physically and symbolically. The research was conducted in two elementary schools in the municipalities of Serra and Vila Velha, exclusively with teachers and in Afrikan matrix territories, involving priests, temple workers, and parents of Afrikan matrix students. The aim was to understand their perspectives on how the curriculum excludes and erases the identities of these students, and whether, in their view, it addresses or invisibilizes Afrikan bodies, their cultural demands, and how schools perceive traditional Afrikan matrix knowledge, as confirmed by Law 10.639- 2003. The study used qualitative empirical research methodology with a decolonial approach, employing the method of observation-intervention in a dialogical perspective. As Afrikan traditions demonstrate, there is no separation between the elements of society, thus there is a direct relationship between the researcher and the object being researched. Through narratives and writing-experiences, the study proposes new perspectives and possibilities of existence, re existence, and epistemic insurgency. Data collection was conducted with two Candomblé priestesses, both of whom are also educators, parents of students who attend the same temple, and seven teachers from two public schools in the municipality of Vila Velha. The results were analyzed based on the theoretical framework used, demonstrating how traditional Afrikan matrix knowledge can be powerful tools for propagating knowledge and affirming the Afrikan matrix identity in Brazil